Complement C5b-9 and Cancer: Mechanisms of Cell Damage, Cancer Counteractions, and Approaches for Intervention - Fishelson, Zvi; Kirschfink, Michael (Frontiers in Immunology, 2019)
The interactions of cancer cells with components of the complement system are highly complex, leading to an outcome that is either favorable or detrimental to cancer cells. Currently, we perceive only the ‘tip of the iceberg’ of these interactions. In this review, we focus on the complement terminal C5b-9 complex, known also as the complement membrane attack complex (MAC) and discuss the complexity of its interaction with cancer cells, starting with a discussion of its proposed mode of action in mediating cell death, and continuing with a portrayal of the strategies of evasion exhibited by cancer cells, and closing with a proposal of treatment approaches targeted at evasion strategies. Upon intense complement activation and membrane insertion of sufficient C5b-9 complexes, the afflicted cells undergo regulated necrotic cell death with characteristic damage to intracellular organelles, including mitochondria, and perforation of the plasma membrane. Several pro-lytic factors have been proposed, including elevated intracellular calcium ion concentrations and activated JNK, Bid, RIPK1, RIPK3, and MLKL; however, further research is required to fully characterize the effective cell death signals activated by the C5b-9 complexes. Cancer cells over-express a multitude of protective measures which either block complement activation, thus reducing the number of membrane-inserted C5b-9 complexes, or facilitate the elimination of C5b-9 from the cell surface. Concomitantly, cancer cells activate several protective pathways that counteract the death signals. Blockage of complement activation is mediated by the complement membrane regulatory proteins CD46, CD55, and CD59 and by soluble complement regulators, by proteases that cleave complement proteins and by protein kinases, like CK2, which phosphorylate complement proteins. C5b-9 elimination and inhibition of cell death signals are mediated by caveolin and dynamin, by Hsp70 and Hsp90, by the mitochondrial stress protein mortalin, and by the protein kinases PKC and ERK. It is conceivable that various cancers and cancers at different stages of development will utilize distinct patterns of these and other MAC resistance strategies. In order to enhance the impact of antibody-based therapy on cancer, novel precise reagents that block the most effective protective strategies will have to be designed and applied as adjuvants to the therapeutic antibodies.